Nature of Indonesia’s Deindustrialization - Muhammad Irfan Islami; Fithra Faisal Hastiadi (Economics Development Analysis Journal, 2020)
This research aims to identify the nature of deindustrialisation on Indonesia’s economy. To test the negative deindustrialisation, this research performed a descriptive analysis on value-added, export-import, and productivity data of manufacturing sector. To test the premature deindustrialisation, this research conducted a regression analysis to create a simulation of value of GDRP per capita at the top of industrialization taken place on Indonesia’s economy. Descriptive analysis shows that deindustrialization in Indonesia prevails with downward trend of value-added, trade performance, and productivity of manufacturing sector. Subsector analysis also shows that manufacturing subsectors having high value added experienced negative trend in all mentioned indicators. The result of premature deindustrialization model regression shows that the peak of industrialization in Indonesia achieved at lower level income per capita compared to several thresholds of premature deindustrialization. Those results show that negative and premature deindustrialisation prevailed in Indonesia’s economy. The consequence of these research’s results is to promote the politics of reindustrialization. There are several recommendations for policy makers to enhance performance of manufacturing sector. From demand-side, it is important to expand market of manufacturing product internationally and domestically. From supply side, the policy makers should increase the investments and insentives for businesses.